The Clostridium difficile PCR ribotype 027 lineage: a pathogen on the move. (28th April 2014) - Valiente, E.; Cairns, M. D.; Wren, B. W.
Abstract Clostridium difficile is a Gram‐positive, spore‐forming, human and animal pathogen that is the major cause of antibiotic‐associated diarrhoea worldwide. The past decade has seen the rapid emergence of the hypervirulent PCR ribotype (RT) 027 complex, which has been associated with increases in the incidence and severity of disease and mortality. In this review, we describe the potential virulence factors that have been reported in strains from the RT 027 complex. We review the emergence, population structure, dissemination and evolution of this lineage.